Identification of naturally occurring drug-resistant mutations of SARS-CoV-2 papain-like protease - Haozhou Tan; Qianru Zhang; Kyriakos Georgiou; Siyu Zhang; Kan Li; George Lambrinidis; Antonios Kolocouris; Xufang Deng; Jun Wang (Nature Communications)
Abstract The SARS-CoV-2 papain-like protease (PLpro) is a cysteine protease that cleaves viral polyproteins and antagonizes the host immune response during viral replication. Jun12682 and PF-07957472 are the first-in-class PLpro inhibitors showing potent in vivo antiviral efficacy in mouse models. In this study, we characterize naturally occurring mutations at residues located at the drug-binding site of Jun12682. The results reveal several PLpro mutants showing significant drug resistance while maintaining comparable enzymatic activity as the wild-type PLpro. The physiological relevance of the identified drug-resistant mutants, including E167G and Q269H, is validated through independent serial viral passage experiments. Molecular dynamics simulations and perturbative free energy calculations show that drug-resistant PLpro mutants weaken hydrogen bonding and π-π stacking interactions. Collectively, this study identifies E167, Y268, and Q269 as drug-resistant hotspots for PLpro inhibitors that bind to the BL2 loop and groove region, which are valuable in informing the design of the next-generation PLpro inhibitors.